2004
DOI: 10.1021/jp048687n
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Confined Water in AlPO4-5 Zeolite

Abstract: The structural and dynamic properties of confined water in AlPO 4 -5 zeolite (Ø ) 7.3 Å) have been investigated by neutron scattering experiments during the adsorption process. Our aim is to elucidate the peculiar behavior of confined water at the nanoscopic confinement range. Confined water presents unusual properties in comparison with other sorbate species such as deuterium or methane. Even in the nanoporous diameter range, the water sorption phenomenon looks like the so-called "capillary condensation" phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 43 publications
6
63
1
Order By: Relevance
“…At such mesoscopic scale, numerous studies have shown that the structure and the physical properties of confined liquids in cavities differ strikingly from the bulk system [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The experiments on the confinement of water or associated liquid such as alcohol in mesoporous materials (aerogels, controlled pore glass, MCM-41.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At such mesoscopic scale, numerous studies have shown that the structure and the physical properties of confined liquids in cavities differ strikingly from the bulk system [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The experiments on the confinement of water or associated liquid such as alcohol in mesoporous materials (aerogels, controlled pore glass, MCM-41.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous investigations have been devoted on the understanding of confined water and other liquids into mesoporous materials such as MCM-41, Vycor, clay and porous silicon [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These studies have revealed effects of confinement which affect both the structure and dynamics of the confined system of which properties differ strictly from these-ones of bulk liquid [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Surfactant systems self assemble into a variety of structures which present particular organizations of the membranes and provide model system to host small or significant amounts of water for mimic confinement in biological objects [1,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The sorption and structure of water molecules in calcined microporous aluminophosphates have been widely studied; [14][15][16] it was found that water molecules adopt interesting helicoidal structures with double (in AlPO-5 [17] ) or triple (in VPI-5 [18,19] ) water helices, stabilised by H-bond networks. However, these structural studies usually considered adsorption of water in the structures in post-synthetic steps (after calcination of the SDA molecules used to obtain the microporous material).…”
Section: Introductionmentioning
confidence: 99%
“…12,14) It is considered that H 2 O molecules are adsorbed in the pore of AlPO 4 -5 and the water vapor adsorption increases sharply at the P/P 0 = 0.25 because of the strong interaction between H 2 O molecules in the AlPO 4 -5 pore due to the hydrogen bond. 8) Adsorption isotherms of water vapor in the aluminum dross-derived AlPO 4 -5 are shown in Figs. 8, 9 and 10.…”
Section: Hydrothermal Synthesis Of Alpo 4 -5mentioning
confidence: 99%